Developmental Adaptation of Rat Nociceptive Withdrawal Reflexes after Neonatal Tendon Transfer - Holmberg, Hans (J Neurosci, 1997)
Nociceptive withdrawal reflexes (NWRs) were studied in adult rats in which the movement patterns produced by single muscles had been altered by neonatal tendon transfer. NWRs evoked by cutaneous noxious mechanical and thermal (CO(2)-laser) stimulation were recorded using electromyography in a decerebrate spinal preparation. The sensitivity distribution within the receptive fields of the NWRs of the extensor digitorum longus and the peronei muscles exhibited changes corresponding to the altered movement patterns. No detectable change of NWRs was found in normal muscles whose receptive fields overlapped that of the modified muscle. Furthermore, NWRs of muscles that regained an essentially normal function after neonatal tendon transfer did not differ from normal. It is proposed that a developmental experience-dependent mechanism, which takes into account the hindlimb movement pattern caused by contraction of single muscles, underlies the functionally adapted organization of adult NWRs.